Action of nitromezuril against Eimeria tenella with clinically anticoccidial indices and histopathology - She, Rufeng; Fei, Chenzhong; Chen, Huiya; Wang, Xiaoyang; Wang, Mi; Zhang, Keyu; Zhang, Lifang; Wang, Chunmei; Liu, Yingchun; Zheng, Wenli; Xue, Feiqun (Parasitology research (1987), 2017)
Nitromezuril is a novel triazine compound for preventing coccidiosis in broiler chickens. A single treatment of chickens inoculated with Eimeria tenella during the endogenous phase were used to evaluate the developmental stages of action of nitromezuril by clinically anticoccidial indices and histopathology. Results showed that a single dose of nitromezuril at 5 mg/kg b.w. during 56 to 80 h post-inoculation can most effectively prevent weight loss and reduce both oocyst shedding and caecal lesions. The anticoccidial index reached the level of middle efficacy. Histological examinations indicated that administration of nitromezuril during 44 to 104 h after infection significantly reduced the merozoite population and the pathological damage to the caecum. Nitromezuril treatment could disturb the process of schizonts division into schizoites and produce abnormal schizonts. Overall, nitromezuril may exert its effects during the entire endogenous stage of the parasites but the schizogony stages were intrinsically more vulnerable. Nitromezuril is a potential novel anticoccidial agent suitable for further development.